Upaya Pengembangan Potensi Wisata Cengkir Manis Bernuansa Edukasi Di Desa Tanjungrejo - Maulida, Savita Rizky; Ismaya, Erik Aditia; Roysa, Mila (The Indonesian Journal of Social Studies, 2021)
The development of tourism potential with educational nuances is an effort to develop a tourism potential in which there are several vehicles that can foster character values in children. This study describes the development of the potential for Cengkir Manis Tourism with educational nuances in Tanjungrejo Village. This study uses a qualitative descriptive method as a stage in carrying out research. The subjects in this research are managers of tourist attractions, visitors to tourist attractions, and sellers at tourist attractions. This research uses data collection techniques that include the observation stage, the interview stage, the documentation and recording stages. The data analysis used is descriptive qualitative data analysis. The results showed that the manager had planned to develop the tourism potential in Cengkir Manis Tourism. In connection with the existence of the development plan, Cengkir Manis Tourism can also be used as a tourist place or tourist attraction with an educational concept for tourist visitors and also for children, because there are several rides that are interesting and challenging and have educational value such as fostering a character of curiosity, character self-confidence, and also the character of courage.